Laser power meters as an X‐ray power diagnostic for LCLS‐II. (11th December 2017) - Heimann, Philip; Moeller, Stefan; Carbajo, Sergio; Song, Sanghoon; Dakovski, Georgi; Nordlund, Dennis; Fritz, David
Abstract : Laser power meters are being developed as a compact X‐ray power diagnostic for LCLS‐II and are characterized for their responsivity, linearity and vacuum compatibility. The power meters are calibrated against X‐ray photodiodes and a gas monitor detector. Abstract : For the LCLS‐II X‐ray instruments, laser power meters are being developed as compact X‐ray power diagnostics to operate at soft and tender X‐ray photon energies. These diagnostics can be installed at various locations along an X‐ray free‐electron laser (FEL) beamline in order to monitor the transmission of X‐ray optics along the beam path. In addition, the power meters will be used to determine the absolute X‐ray power at the endstations. Here, thermopile power meters, which measure average power, and have been chosen primarily for their compatibility with the high repetition rates at LCLS‐II, are evaluated. A number of characteristics in the soft X‐ray range are presented including linearity, calibrations conducted with a photodiode and a gas monitor detector as well as ultra‐high‐vacuum compatibility tests using residual gas analysis. The application of these power meters for LCLS‐II and other X‐ray FEL sources is discussed.